2016
DOI: 10.1099/jgv.0.000363
|View full text |Cite
|
Sign up to set email alerts
|

The levels of epithelial anchor proteins β-catenin and zona occludens-1 are altered by E7 of human papillomaviruses 5 and 8

Abstract: Infection with viruses of the genus Betapapillomavirus, b-human papillomaviruses (b-HPV), is implicated in the development of non-melanoma skin cancer. This was first evidenced for HPV5 and HPV8 in patients with the skin disease epidermodysplasia verruciformis (EV). The relocalization of the junctional bridging proteins b-catenin and zona occludens-1 (ZO-1) from the adherens and tight junctions are common processes of the epithelial-mesenchymal transition (EMT) associated with tumour invasion. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Infection of PM1 cells was performed as described before. 36,37 RNA isolation, reverse transcription and real-time PCR…”
Section: Cer-e2mut-fw: Cagaacaaacactttaggcacagattgcgc;mentioning
confidence: 99%
“…Infection of PM1 cells was performed as described before. 36,37 RNA isolation, reverse transcription and real-time PCR…”
Section: Cer-e2mut-fw: Cagaacaaacactttaggcacagattgcgc;mentioning
confidence: 99%
“…At the molecular level, this involves a reorganization of cell-cell adhesion complexes and modifications in cell-matrix interactions. Related to cell-cell connections, HPV8-E7 possesses the capacity to deregulate cell-cell junctions through the upregulation of β-catenin, zona occuldens protein 1 (ZO-1) [ 21 ], and the AKT serine/threonine kinase 2 (AKT2) [ 17 ]. Studies based on cell-matrix interactions revealed that the ECM proteins collagen IV, laminin V, and fibronectin all trigger HPV8-E7-mediated invasion.…”
Section: Invasion Is Regulated Both At the Level Of The Tumor Cellmentioning
confidence: 99%
“…Moreover, it induces changes in the expression of cell junction proteins, like E-cadherin at the adherens junctions [22,23]. Apart from that, E7 proteins derived from cutaneous HPVs increase the abundance of epithelial anchor proteins, such as β-catenin and zona occludens-1 [24]. These findings altogether suggest still underexplored activities of HPV E7 associated to alterations in cell-to-cell contacts and polarity that deserve further investigation.…”
Section: Introductionmentioning
confidence: 97%